1997
DOI: 10.1164/ajrccm.156.1.9606040
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Neural Nitric Oxide-mediated Relaxation after Antigen Exposure in Guinea Pig Airwaysin vitro

Abstract: Nitric oxide (NO), a neurotransmitter of inhibitory nonadrenergic noncholinergic (iNANC) nerves in airways, is a radical with a short half-life, and its function may be modified by airway inflammation. To test this hypothesis, we examined whether airway allergic inflammation affects iNANC responses mediated by NO in guinea pigs in vitro. Animals sensitized with ovalbumin (OA) were challenged with 0.03% OA (OA group) or saline (saline group) by inhalation on 3 consecutive days. On the day after the final challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…21 Deficiency of NO can induce airway hyperresponsiveness, as shown in allergen-challenged guinea pigs. [22][23][24] With low concentrations of arginine, NOS generates superoxide and NO that interact to form peroxynitrite, which leads to airway cell injury. 25 Another potential mechanism for a role of arginase in asthma pathogenesis relates to increasing production of ornithine, a precursor of polyamines (ie, putrescine, spermidine, and spermine) and proline.…”
Section: Discussionmentioning
confidence: 99%
“…21 Deficiency of NO can induce airway hyperresponsiveness, as shown in allergen-challenged guinea pigs. [22][23][24] With low concentrations of arginine, NOS generates superoxide and NO that interact to form peroxynitrite, which leads to airway cell injury. 25 Another potential mechanism for a role of arginase in asthma pathogenesis relates to increasing production of ornithine, a precursor of polyamines (ie, putrescine, spermidine, and spermine) and proline.…”
Section: Discussionmentioning
confidence: 99%
“…1) [77,96,97]. A deficiency of cNOS activity and endogenous bronchodilating NO contributing to AHR was also demonstrated after repeated allergen challenge of sensitised guinea pigs [98,99]. Importantly, it was demonstrated that a reduction in cNOS-derived NO may also contribute to AHR in patients with severe asthma [100], and may similarly be induced by allergen exposure [101].…”
Section: Acute Modulation Of Ahrmentioning
confidence: 97%
“…Furthermore, it has been noted that the circadian variations of the iNANC response may contribute to overnight bronchoconstriction in patients with nocturnal asthma (274). Neural NO-induced relaxation is impaired in guinea pig airways after allergen exposure, without affecting nNOS expression, suggesting a reduced neural NOS activity when allergic inflammation is exacerbated (296).…”
Section: No and Inancmentioning
confidence: 99%